Testing and Characterization of a MEMS Micro-Cantilever System - Kafumbe, Said; Alun, Harris; Jim, Burdess (IEEE., 2016)
The testing and characterization of micro-electro-mechanical systems (MEMS) cantilever arrays of average thickness 2.2 ± 0.04 µm, width 52.06 ± 1.93 µm and lengths varying between 390 - 1490 µm, is presented. A novel optical workstation with combining both a surface profiler and a laser vibrometer, was used for the experimental setup. Both static and dynamic tests were performed in characterizing and evaluating the functionality of the fabricated devices using piezo and electrostatic actuation. The static deflection under electrostatic voltage of 10.2 V and 56.4 V was 150 ± 15 nm, and 760 ± 65 nm respectively for a cantilever of nominal length of 390 µm. The shortest beam of nominal length of 390 µm resonated at 4.417 kHz using an electrostatic actuation mechanism with a 0.01 % discrepancy whereas the longest beam of nominal length of 1490 µm resonated at 316.5 Hz with a 0.03 % discrepancy. However using the piezo actuation, the resonance frequency of the shortest and longest cantilevers was 4.515 kHz and 303.82 kHz respectively. The difference from the predicted values was 0.008 % for the shortest beam, and 0.01% for the longest one. All results showed the beams were functioning perfectly for applications in radio frequency tuning.
Keywords: MEMS; cantilevers; electrostatic actuation; piezo electric actuation